Azobenzene‐containing LC polymethacrylates highly photosensitive in broad spectral range. Issue 18 (14th June 2016) - Bobrovsky, Alexey; Shibaev, Valery; Cigl, Martin; Hamplová, Vĕra; Pociecha, Damian; Bubnov, Alexej
ABSTRACT: Two photosensitive chiral liquid crystalline azobenzene‐containing polymethacrylates having different length of flexible spacer connecting chromophores with backbone were synthesized and their phase behavior and photo‐optical properties were studied. Both polymers consist of lateral methyl substituents in ortho ‐position of azobenzene chromophores providing high photosensitivity even in red spectral region as well as high thermal stability of photoinduced Z ‐form of azobenzene chromophores. It is shown, that smectic phase (SmA*) formation in films of polymer with longer spacer predetermines its quite unusual spectral response to UV and subsequent visible light actions. The SmA* phase promotes spontaneous homeotropic alignment of azobenzene chromophores in polymer films. UV‐irradiation induces not only E‐Z isomerization but also results in disruption of homeotropic alignment, whereas subsequent visible light action enables to obtain films with the low degree of chromophores orientation. The photo‐orientation phenomena under the action of polarized light of different wavelength on polymer films were studied. The possibility of using red polarized light of moderate intensity for optical photorecording on polymer films is demonstrated. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2962–2970 Abstract : Two photosensitive liquid crystalline azobenzene‐containing polymethacrylates, having different lengths of flexible spacer connecting chromophores with backbone spacers, were synthesized and their phase behavior and photo‐optical properties were studied. The presence of lateral methyl substituents in ortho ‐position of azobenzene chromophores provides high photosensitivity even in red spectral region. The photo‐orientation phenomena under the action of polarized light of different wavelengths were studied and the possibility of optical photorecording on polymer films is demonstrated.